Dynamics of Household Driving Demand - Hill, Daniel H. (The Review of Economics and Statistics, 1986)
A bstract-A statistical model of household automotive transportation demand is developed which nests the Koyck distributed lag model and four alternatives as special cases. These various specifications are tested with data from the Panel Study of Income Dynamics. For households who changed residence during the observation period 1973-1978, the Koyck model is rejected in favor of a model which allows price and income effects to vary freely for two years prior to settling into a geometric declining pattern. The maximum single year income impact, for these households, is in the year following the income change. Prices appear to have an initial negative impact on miles driven followed by a strong positive impact in the third year. This latter effect may be related to the acquisition of a more fuel efficient vehicle stock.